DESIGNING A SCADA-BASED MONITORING AND CONTROL SYSTEM FOR A SOLAR-POWERED LIVESTOCK FEED PRODUCTION MACHINE - Yosua Surya Karuh; I Gede Para Atmaja; Johan Makal; Siti Maisaroh (CV. TOTUS TUUS, 2026)
Livestock feed production in small- and medium-scale farming still relies heavily on manual control and limited energy monitoring, resulting in operational inefficiency, higher production costs, and difficulty in tracking real-time electricity consumption. This study aimed to design a Supervisory Control and Data Acquisition (SCADA)-based monitoring and control system for a livestock feed production machine integrated with a solar photovoltaic power system. The research employed a Research and Development approach, involving problem identification, literature review, descriptive field analysis, hardware and software design, PLC ladder diagram development, and Human Machine Interface dashboard design. The proposed system integrates key SCADA components, including PLC, HMI, sensors, power meter, communication modules, and photovoltaic energy support. The design results show that the system can monitor electrical parameters such as voltage, current, power, energy consumption, and frequency in real time. The HMI dashboard enables operators to access data through tables, graphs, historical records, control menus, and alarm threshold settings. The study concludes that integrating SCADA with solar-powered livestock feed production technology can improve monitoring accuracy, operational efficiency, system safety, and energy sustainability. This research contributes to the development of smart farming technology by offering a conceptual model for automated, renewable-energy-based production systems. Future studies should focus on prototype implementation, field testing, cost-benefit analysis, and performance evaluation under different livestock production conditions.